ATG5: A central autophagy regulator implicated in various human diseases. (5th September 2022) - Changotra, Harish; Kaur, Sargeet; Yadav, Suresh Singh; Gupta, Girdhari Lal; Parkash, Jyoti; Duseja, Ajay
Abstract: Autophagy, an intracellular conserved degradative process, plays a central role in the renewal/recycling of a cell to maintain the homeostasis of nutrients and energy within the cell. ATG5, a key component of autophagy, regulates the formation of the autophagosome, a hallmark of autophagy. ATG5 binds with ATG12 and ATG16L1 resulting in E3 like ligase complex, which is necessary for autophagosome expansion. Available data suggest that ATG5 is indispensable for autophagy and has an imperative role in several essential biological processes. Moreover, ATG5 has also been demonstrated to possess autophagy‐independent functions that magnify its significance and therapeutic potential. ATG5 interacts with various molecules for the execution of different processes implicated during physiological and pathological conditions. Furthermore, ATG5 genetic variants are associated with various ailments. This review discusses various autophagy‐dependent and autophagy‐independent roles of ATG5, highlights its various deleterious genetic variants reported until now, and various studies supporting it as a potential drug target. Significance statement: ATG5, a candidate protein in autophagy, plays an important role during autophagosome formation. Apart from that, ATG5 also plays autophagy‐independent, significant, diverse roles in essential physiological processes and is involved in various pathological conditions. No review is available that has focused comprehensively on the roles of ATG5 in various human diseases. Therefore, the central idea of this review is to highlight the multifaceted roles of ATG5 by providing detailed coverage of available information and providing in‐depth knowledge about its various interacting partners and molecules. This further can provide several ways by which its interactions could be regulated and therapeutically targeted to restrict deleterious pathways and prevent disease development.